UTILIZATION OF INFORMATION TECHNOLOGY FOR REALIZATION OF GOOD GOVERNANCE IMPLEMENTATION IN THE PILOT PROJECT AREA AT RAJABASA IN BANDAR LAMPUNG - Purwiyanti, Sri; Yuniati, Yetti; Permata, Diah (Universitas Negeri Medan, 2017)
AbstractImplementation of good governance’s principles at Rajabasa, Bandar Lampung has not done well. It caused by the lack of communication between government (public officials) and citizens. Therefore, the purpose of this public service activity is to resolve the problem by using information technology. The activity chooses a smaller government scope, which is a neighborhood area. The activity involves two steps, which is website creation and training step. The website contains are statistic data of citizens, procedures to apply the resident documents completing with the required forms, activities announcement, interactive forum for conveying critics and suggestions between citizens and government, and promotion forum for industry players. As a result, the website successfully displays a variety of information needed by citizens, and provides a means of communication for citizens and public officials. Training step about procedure for using the website also has been done. Certainly, evaluation about the liveliness of citizens in accessing the website is still required. However, good communication, efficiency, and effectiveness can begin to form well, which leads to better implementation of good governance.Keywords: good governance, information technology, public service